Impact of Mangosteen Peel and Centella asiatica on Cognitive Function in Healthy Older Adults - Fitriana, Lisna Anisa; Rahmi, Upik; Ghaida, Nafisa Siti; Komarudin, Komarudin; Fitri, Mustika (Universitas Pendidikan Indonesia, 2025)
Introduction: The increasing elderly population in Indonesia is accompanied by a growing risk of cognitive decline and dementia. Current pharmacological interventions have limited effectiveness and may cause adverse effects, highlighting the need for safe, natural-based alternatives. Mangosteen peel (Garcinia mangostana) and gotu kola (Centella asiatica) possess neuroprotective, antioxidant, and anti-inflammatory properties that may enhance cognitive function in older adults. Objective: This study aimed to evaluate the effectiveness of mangosteen peel and Centella asiatica extract supplementation in improving cognitive function among the elderly. Methods: A quasi-experimental pretest–posttest two-group study was conducted among 26 elderly residents at Griya Lansia Garut selected by purposive sampling. The intervention group received combined mangosteen peel and Centella asiatica supplementation for four weeks. Cognitive function was measured using MMSE, TMT-A, and Forward Digit Span, with data analyzed using Wilcoxon and Mann–Whitney tests (p0.05). Results: The intervention group showed significant improvements in MMSE scores (Δ=2.15; p0.001), processing speed and attention as measured by TMT-A (p=0.021), and working memory as measured by Forward Digit Span (p0.001). Between-group comparisons revealed significant differences in MMSE (p0.001) and TMT-A score changes (p=0.008), whereas no significant difference was observed for Forward Digit Span (p=0.458). Conclusion: Supplementation with mangosteen peel and Centella asiatica extracts may improve global cognitive function and attention in elderly individuals. This combined botanical intervention shows promise as a supportive non-pharmacological strategy for preventing cognitive decline; however, larger randomized controlled trials are required to confirm its efficacy and safety.